2019
DOI: 10.1111/jph.12789
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of lineages within “Colletotrichum gloeosporioides s.l.” associated with cassava anthracnose disease by BOX‐ and ERIC‐PCRs

Abstract: Several molecular techniques have been used to differentiate species or genetic lineages of microorganisms prior to sequencing. Among them, BOX-and ERIC-PCRs may provide specific banding patterns for different species, allowing its differentiation.Therefore, the objective of this study was to evaluate these techniques as a tool for differentiation of phylogenetic lineages belonging to the Colletotrichum gloeosporioides species complex associated with cassava anthracnose disease. Sets of BOX-and ERIC-PCR primer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…However, its production is strongly limited by many pests where cassava anthracnose disease (CAD), caused by Colletotrichum spp., is considered one of the most destructive cassava leaf diseases especially in main cassava producing countries worldwide (William et al 2012;Sangpueak et al 2018) CAD is characterized by cankers on stems, branches, fruits, leaf spots, and diebacks on aerial parts of diseased plants (Kunkeaw et al 2010;Silva et al 2018). Despite the recent reports of different Colletotrichum species associated with cassava antracnose in Brazil (Bragança et al 2016;Oliveira et al 2016Oliveira et al , 2018Silva et al 2019), little is known about its distribution, incidence, prevalence and disease severity across different production regions. Furthermore, there are no data regarding the relationship of CAD incidence and severity and agroecological practices and/or climatic zones in Brazilian conditions.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, its production is strongly limited by many pests where cassava anthracnose disease (CAD), caused by Colletotrichum spp., is considered one of the most destructive cassava leaf diseases especially in main cassava producing countries worldwide (William et al 2012;Sangpueak et al 2018) CAD is characterized by cankers on stems, branches, fruits, leaf spots, and diebacks on aerial parts of diseased plants (Kunkeaw et al 2010;Silva et al 2018). Despite the recent reports of different Colletotrichum species associated with cassava antracnose in Brazil (Bragança et al 2016;Oliveira et al 2016Oliveira et al , 2018Silva et al 2019), little is known about its distribution, incidence, prevalence and disease severity across different production regions. Furthermore, there are no data regarding the relationship of CAD incidence and severity and agroecological practices and/or climatic zones in Brazilian conditions.…”
mentioning
confidence: 99%
“…The study of genetic diversity of plant pathogens and species to identify and characterize causal agents of diseases is a key point for selection of adequate isolates for screening of resistance in plant breeding programs (Ramdial and Rapersad 2015). More recently, Silva et al (2019) demonstrated that enterobacterial repetitive intergenic consensuspolymerase chain reaction markers (ERIC-PCR) can be used as a complementary tool for discrimination of species within the Colletotrichum gloeosporioides complex associated with CAD in Brazil with a very high correlation with multilocus phylogenetic analysis.…”
mentioning
confidence: 99%
See 3 more Smart Citations